Integrasi Nilai-Nilai Pendidikan Damai dalam Pelaksanaan Pembelajaran Akidah Akhlak di Madrasah Aliyah Kabupaten Pidie - Mardhiah, Ainul; Mutia, Sri (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
This study aims to analyze and explore the integration of peace education values in the teaching of Akidah Akhlak at Madrasah Aliyah (MA) in Pidie Regency. Peace education is expected to shape students’ character, not only making them religiously devout but also tolerant and sensitive to diversity. This research employs a qualitative approach with data collection methods including observation, interviews, and documentation. The collected data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings of the study indicate that peace education values, such as tolerance, mutual respect, harmony, and ethics in sosial interaction, have been integrated into the planning of Akidah Akhlak lessons at MA Pidie, through both the syllabus and Lesson Plans (RPP). In the teaching process, teachers impart these values through methods involving group discussions and interactive activities. The assessment of students’ attitudes is carried out using rubrics that encompass aspects of honesty, responsibility, discipline, and cooperation, which reflect peace education values. This study concludes that the integration of peace education values in Akidah Akhlak lessons can contribute to shaping students’ better character and creating a harmonious learning environment. This research contributes to the development of a more responsive religious education curriculum and serves as a reference for educators and policymakers in designing teaching strategies based on peace values. Abstrak Penelitian ini bertujuan untuk menganalisis dan mengeksplorasi integrasi nilai-nilai pendidikan damai dalam pembelajaran Akidah Akhlak di Madrasah Aliyah Pidie. Pendidikan damai diharapkan dapat membentuk karakter siswa yang tidak hanya taat beragama, tetapi juga toleran dan peka terhadap keberagaman. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data melalui observasi, wawancara, dan dokumentasi. Data yang terkumpul dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa nilai-nilai pendidikan damai, seperti toleransi, saling menghargai, kerukunan, dan etika bergaul, telah terintegrasi dalam perencanaan pembelajaran Akidah Akhlak di MA Pidie, baik melalui silabus maupun Rencana Pelaksanaan Pembelajaran (RPP). Dalam pelaksanaan pembelajaran, guru mengajarkan nilai-nilai tersebut melalui metode yang melibatkan diskusi kelompok dan aktivitas interaktif. Penilaian sikap siswa dilakukan menggunakan rubrik yang mencakup aspek kejujuran, tanggung jawab, disiplin, dan kerja sama, yang mencerminkan nilai-nilai pendidikan damai. Penelitian ini menyimpulkan bahwa integrasi nilai-nilai pendidikan damai dalam pembelajaran Akidah Akhlak dapat membantu membentuk karakter siswa yang lebih baik dan menciptakan suasana pembelajaran yang harmonis. Penelitian ini memberikan kontribusi dalam pengembangan kurikulum pendidikan agama yang lebih responsif terhadap tantangan zaman, serta sebagai referensi bagi pendidik dan pembuat kebijakan dalam merancang strategi pembelajaran berbasis nilai-nilai damai.